Jorge Flores Ochoa, a vast anthropological work made from and for the Southern Peruvian Andes - Salas Carreño, Guillermo (2020)
Recently, on August 20, 2020, Dr. Jorge A. Flores Ochoa passed away. He has been a fundamental figure in Cuzco and Peruvian anthropology due to his multiple merits as a researcher, professor, engaged intellectual and tireless cultural animator. This text reviews his main research themes and interests, in particular his notable contributions and constant study of Andean pastoralist societies and, associated with this, his studies regarding the management of  andean agro-ecological complexity. The article then moves to his research on Cuzco’s colonial and republican art and material culture, his ethnography of the city’s and region’s religious celebrations, his broader contributions to the anthropology of the city of Cuzco and his interpretations and analysis on the history and importance of contemporary Cuzco Incanism.